PROVISION OF PREFERENTIAL LOANS TO WOMEN ENTREPRENEURS WITH THE INTEGRATION OF FINANCIAL LITERACY EDUCATIONAL PROGRAMS - Maksudkhujaeva , Dilshodakhon (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
This thesis examines the initiative of providing preferential loans to women entrepreneurs in the Republic of Uzbekistan with the mandatory integration of financial literacy educational programs. This approach aims to promote women’s financial independence, develop entrepreneurial potential, and enhance their economic participation. The study emphasizes that the combination of credit support and financial education contributes to financial inclusion and serves as an important factor in sustainable economic growth.